Extensive Postradiation Ocular and Diffuse Cranial Neuromyotonia Mimicking Myasthenia Gravis. Issue 5 (September 2016) - Hardy, Todd A.; Lee, Andrew W.; Yiannikas, Con; Chen, Celia S.; Reddel, Stephen W.
Abstract : Background: Ocular neuromyotonia is a rare, but well-recognized, complication of cranial irradiation. Case Report: Using figures and videos, we report a 52-year-old man with extensive ocular, brainstem, and lower cranial nerve neuromyotonia postradiation therapy for a fourth ventricle glioma who, in the context of an apparently positive edrophonium test, was initially misdiagnosed with myasthenia gravis. Conclusions: This is the first case of postirradiation neuromyotonia to be reported with such extensive cranial nerve and brainstem involvement. Abstract : Supplemental Digital Content is available in the text.